ANALIZE DIE CASTING PROCESS AND STRUCTURE OF MOLDING FOR INTERNAL COMBUSTION ENGINE VEHICLE - Muhammad Yusuf Nurfani; Ramadhan, Abdul Rahman Agung (Asosiasi Dosen Muda Indonesia, 2023)
Die casting is part of manufacturing process for making metal product, especially internal combustion engine of vehicle. Molding is component for making product from metallurgy process or polymer process. Basically, all part of molding process will be using 3 conditions of process. First is solid raw material for process production, second is melting process of raw material for making product using molding and third is solid for part of finish product after process molding process. In this research will analyze of molding process and structure of engine for internal combustion engine vehicle. Mold casting will be using specification for SUV capacity 2.7L. basic raw material is silica sand, resin, bentonite, and sea coal. The result show that after process mixing optimal pressure from machine to molding is 109675,8 N. and spot test check result show that, after process die casting no any crack founding by 10 specimens of engine of vehicle.